Issues and challenges in society 5.0: humanising human for sustainable future - Abdul Rahman, Shukran (2019)
General Objectives This session addresses the roles of behavioral sciences in developing and improving the quality of human life. It highlights the application of behavioral sciences in designing suitable interventions to humanise human for sustainable future Specific Objectives 1. To introduce Society 5.0 as the latest type of society. 2. To discuss issues and challenges encountered by the current society 3. To deliberate the concept of Humanising Human; and its importance 4. To discuss the roles of Psychology in relation to the Sustainable Development Goals